2021
DOI: 10.3390/en14165115
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Metal Oxide and Polytriarylamine: A Design Principle to Improve the Stability of Perovskite Solar Cells

Abstract: In the last decade, perovskite photovoltaics gained popularity as a potential rival for crystalline silicon solar cells, which provide comparable efficiency for lower fabrication costs. However, insufficient stability is still a bottleneck for technology commercialization. One of the key aspects for improving the stability of perovskite solar cells (PSCs) is encapsulating the photoactive material with the hole-transport layer (HTL) with low gas permeability. Recently, it was shown that the double HTL comprisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…39,40 A similar effect was also observed for this configuration of devices in our previous work. 33 Generally, the efficiency of PSCs with PTTA tends to decrease after 1100 h of operation, whereas PBPyT-based devices demonstrated high operational stability under continuous illumination, which is an encouraging result.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…39,40 A similar effect was also observed for this configuration of devices in our previous work. 33 Generally, the efficiency of PSCs with PTTA tends to decrease after 1100 h of operation, whereas PBPyT-based devices demonstrated high operational stability under continuous illumination, which is an encouraging result.…”
Section: Resultsmentioning
confidence: 81%
“…In order to estimate the potential of conjugated polymers PBPyT-ex and PBPyT-in as HTMs, PSCs with the n-i-p architecture of ITO/SnO 2 /PCBM/MAPbI 3 /HTM/MoO x /Ag were fabricated. 33 The details of PSC fabrication are described in the Experimental section. First, electron-transport layers SnO 2 and PCBM ( [6,6]-phenyl-C 61 butyric acid methyl ester) were spin-coated on the transparent conductive electron-collecting electrode ITO.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, for this experiment, devices with another configuration were fabricated. They consisted of more stable Cs(NH 2 ) 2 CHPbI 3 perovskite, ZnO as ETL, an Al electrode, and vanadium oxide as an inorganic component of the double hole-transport layer [ 14 ]. The evolution of the device efficiency under constant illumination is presented in Figure 5 b.…”
Section: Resultsmentioning
confidence: 99%
“…In recent work, it was demonstrated that the application of a double hole-transport layer comprising a combination of organic material and transition metal oxides in the highest oxidation state, such as molybdenum (VI) oxide, vanadium (V) oxide, and tungsten (VI) oxide allows the achievement of outstanding stabilities of PSCs up to 4500 h under operation conditions [ 13 ]. Furthermore, in our work it was revealed that, while double hole-transport layers with vanadium oxide perform as a perfect encapsulating layer, it is the organic component, which should be optimized further to improve the performance of PSCs [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hole-transporting materials (HTMs) also play a crucial role in boosting performance and improving the operational stability of PSCs. In particular, individual or double-layered HTMs based on a combination of metal oxides and organic polymers can prevent the migration of the volatile byproducts of perovskite reversible decomposition from the device, so they could participate in the perovskite formation reaction enabling improved operation stability of PSCs [ 3 , 4 ]. Many various organic HTMs have recently been developed and investigated in PSCs.…”
Section: Introductionmentioning
confidence: 99%